(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2026)
This paper presents the experience of using repellents to protect against codling moth (Cydia pomonella) in apple orchards in various regions of the Kyrgyz Republic in 2021-2022. Plant protection methods using repellents are practically not used in Kyrgyzstan. Repellents are safe for people and the environment and deserve attention as an alternative pest control option